Вдосконалення функціональних і технологічних рішень для модернізації підігріву сталі в проміжному ковші машини безперервного лиття - Смірнов, О.М.; Нарівський, А.В.; Семірягін, С.В.; Осипенко, В.В.; Семенко, А.Ю.; Скоробагатько, Ю.П. (Physico-technological Institute of Metals and Alloys, 2024)
The using of the system of plasma heating of metal directly in the tundish is quite promising in terms of improving the technology of continuous casting of steel. At the same time, the efficiency of this technology is significantly influenced by the design of the tundish, the location of the plasmatron, the direction of movement of the circulation flows and their speed, the presence of forced mixing of the liquid metal bath, etc. In terms of design, the main technical solutions proposed for plasma heating of steel in a ladle are based on the creation of two-chamber tundish. Moreover, steel is heated in a special receiving chamber. Such heating devices are compact enough to be built into tundish without any significant modifications. Moreover, such heating devices practically do not reduce the useful volume of the tundish. The widespread use of the technology of plasma heating of metal in the tundish of the continuous casting machine (CCM) at a few metallurgical plants in the world is due to the need to increase the stability of the parameters of the casting process and improve the quality of the workpiece while simultaneously reducing specific energy costs. At the same time, additional prerequisites are created for the transformation of the tundish into a multifunctional unit for adjusting the steel temperature and the possibility of its refining. The using of plasma heating in the tundish is especially relevant in the conditions of mini-mills operating technological units of small capacity, for which the implementation of traditional highly efficient solutions for out-of-furnace processing, as well as processing on tundish-furnace units, is not always possible due to the complexity of organizing the heating process, large heat losses and high specific costs of refractories. In addition, such tundish can be quite effective when pouring high-quality grades of steel into billets of small cross-sections, which are produced, as a rule, in relatively small mixer-batches, which makes it difficult to prove them in small steel pouring ladles.